Culture Wars and COVID‐19 Conduct: Christian Nationalism, Religiosity, and Americans' Behavior During the Coronavirus Pandemic. Issue 3 (26th July 2020) - Perry, Samuel L.; Whitehead, Andrew L.; Grubbs, Joshua B.
Abstract: During the COVID‐19 pandemic, Americans' behavioral responses were quickly politicized. Those on the left stressed precautionary behaviors, while those on the (religious) right were more likely to disregard recommended precautions. We propose the far right response was driven less by partisanship or religiosity per se, but rather by an ideology that connects disregard for scientific expertise; a conception of Americans as God's chosen and protected people; distrust for news media; and allegiance to Trump―Christian nationalism. Analyzing panel data collected in the thick of the COVID‐19 crisis, we find Christian nationalism was the leading predictor that Americans engaged in incautious behavior like eating in restaurants, visiting family/friends, or gathering with 10+ persons (though not attending church), and was the second strongest predictor that Americans took fewer precautions like wearing a mask or sanitizing/washing one's hands. Religiosity, in contrast, was the leading predictor that Americans engaged in more frequent precautionary behaviors. Findings document that Christian nationalism, not religious commitment per se, undergirded the far‐right response to COVID‐19 that disregarded precautionary recommendations, thus potentially worsening the pandemic.